2017
DOI: 10.1007/s11483-017-9509-0
|View full text |Cite
|
Sign up to set email alerts
|

Eugenol Nanoencapsulated by Sodium Caseinate: Physical, Antimicrobial, and Biophysical Properties

Abstract: To improve the application of essential oils as natural antimicrobial preservatives, the objective of the present study was to determine physical, antimicrobial, and biophysical properties of eugenol after nanoencapsulation by sodium caseinate (NaCas). Emulsions were prepared by mixing eugenol in 20.0 mg/mL NaCas solution at an overall eugenol content of 5.0-137.9 mg/mL using shear homogenization. Stable emulsions were observed up to 38.5 mg/mL eugenol, which had droplet diameters of smaller than 125 nm at pH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Optimized ultrasound-mediated nettle oil (1.25 wt%) NEs stabilized by purified jujube polysaccharide with 86.75 nm droplet size inactivated the Gram-positive bacterium more effectively than the Gram-negative one (Gharibzahedi 2017). Stable NEs prepared by mixing eugenol with SCas using shear homogenization observed up to 38.5 mg/mL eugenol showed droplet diameters <125 nm at pH 5−9 after ambient storage for up to 30 days and more effective inhibition of E. coli O157:H7 than free eugenol during incubation at 37 °C for 48 h. A greater reduction of intracellular ATP and a greater increase of extracellular ATP was observed in bacteria treated with encapsulated eugenol (20 min interaction at 21 °C) compared to free eugenol suggesting enhanced permeation of eugenol due to its nanoencapsulation, although the possible membrane adaptation could not be excluded (Zhang et al 2018). Salvia-Trujillo et al (2014) reported that lemongrass oil−alginate NEs prepared by microfluidization exhibited enhanced antimicrobial activity against E. coli, while ultrasound processing of NEs led to loss of their bactericidal action.…”
Section: Nanoemulsions Of Essential Oils and Their Constituentsmentioning
confidence: 92%
“…Optimized ultrasound-mediated nettle oil (1.25 wt%) NEs stabilized by purified jujube polysaccharide with 86.75 nm droplet size inactivated the Gram-positive bacterium more effectively than the Gram-negative one (Gharibzahedi 2017). Stable NEs prepared by mixing eugenol with SCas using shear homogenization observed up to 38.5 mg/mL eugenol showed droplet diameters <125 nm at pH 5−9 after ambient storage for up to 30 days and more effective inhibition of E. coli O157:H7 than free eugenol during incubation at 37 °C for 48 h. A greater reduction of intracellular ATP and a greater increase of extracellular ATP was observed in bacteria treated with encapsulated eugenol (20 min interaction at 21 °C) compared to free eugenol suggesting enhanced permeation of eugenol due to its nanoencapsulation, although the possible membrane adaptation could not be excluded (Zhang et al 2018). Salvia-Trujillo et al (2014) reported that lemongrass oil−alginate NEs prepared by microfluidization exhibited enhanced antimicrobial activity against E. coli, while ultrasound processing of NEs led to loss of their bactericidal action.…”
Section: Nanoemulsions Of Essential Oils and Their Constituentsmentioning
confidence: 92%
“…Specifically, soy or whey protein with maltodextrins are frequently applied, generally due to the variety of maltodextrins DE [ 74 ]. Among dairy proteins, sodium caseinate is preferred over other proteins due to its high solubility in water, emulsifying properties with oil and rapid formation of interfacial films and excellent surface activity [ 75 ]. Sodium caseinate has been reported to be the most effective emulsion stabilizer for fats.…”
Section: Optimizing the Encapsulation Process Conditionsmentioning
confidence: 99%
“…[1][2][3][4][5] Nanotechnologies have promoted the development of food safety and quality. For example, antibacterial essential oil emulsions and films were employed for food sterilization, [6][7][8][9][10][11] high-efficiency preservatives and growth regulators were synthesized through nano-assembly to govern food shelf-life and ripening, [12,13] also, sensitive nanosensors were developed to determine harmful and safety uncertain ingredients in food. [14,15] Porous materials have gradually aroused the interest of scientists because of their unique structure and property, and showed great potential in food applications.…”
Section: Introductionmentioning
confidence: 99%